A glossary for research in occupational health. Issue 1 (1st January 2003) - García, A M; Checkoway, H
Abstract : This glossary includes a selection of terms pertaining to the field of research in occupational health. The glossary is mostly addressed to readers not familiarised with the more specific terms used in the study and protection of workers' health. The terms have been ordered according to their logical connections, so the glossary can be read from beginning to end giving the reader an overview on occupational health research main focuses, methods, and applications.